(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease characterized by progressive joint destruction, systemic immune activation, and heterogeneous clinical presentation. Modern research emphasizes the importance of integrated immunological markers for early diagnosis, disease stratification, and therapeutic monitoring. The combination of autoantibody profiling and cytokine analysis allows a deeper understanding of immune mechanisms underlying disease activity and progression. Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease characterized by progressive joint destruction, systemic immune activation, and heterogeneous clinical presentation. Modern research emphasizes the importance of integrated immunological markers for early diagnosis, disease stratification, and therapeutic monitoring. The combination of autoantibody profiling and cytokine analysis allows a deeper understanding of immune mechanisms underlying disease activity and progression. Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease characterized by progressive joint destruction, systemic immune activation, and heterogeneous clinical presentation. Modern research emphasizes the importance of integrated immunological markers for early diagnosis, disease stratification, and therapeutic monitoring. The combination of autoantibody profiling and cytokine analysis allows a deeper understanding of immune mechanisms underlying disease activity and progression. Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease characterized by progressive joint destruction, systemic immune activation, and heterogeneous clinical presentation. Modern research emphasizes the importance of integrated immunological markers for early diagnosis, disease stratification, and therapeutic monitoring. The combination of autoantibody profiling and cytokine analysis allows a deeper understanding of immune mechanisms underlying disease activity and progression. Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease characterized by progressive joint destruction, systemic immune activation, and heterogeneous clinical presentation. Modern research emphasizes the importance of integrated immunological markers for early diagnosis, disease stratification, and therapeutic monitoring. The combination of autoantibody profiling and cytokine analysis allows a deeper understanding of immune mechanisms underlying disease activity and progression.